Skin graft donor site: a procedure for a faster healing - Cuomo, Roberto; Grimaldi, Luca; Brandi, Cesare; Nisi, Giuseppe; D'Aniello, Carlo (Acta Biomedica Atenei Parmensis, 2017)
Background: The authors want to evaluate the efficacy of fibrillary tabotamp dressing in skin graft-donor site. A comparison was made with Vaseline gauzes. Tabotamp is an absorbable haemostatic product of Ethicon (Johnson and Johnson) obtained by sterile and oxidized regenerated cellulose (Rayon). It is used for mild to moderate bleeding. Materials and methods: 276 patients were subject to skin graft and divided into two group: Group A and Group B. The donor site of patients in Group A was medicated with fibrillary tabotamp, while the patients of Group B were medicated only with Vaseline gauze. We recorded infection, timing of healing, number of dressing change, the pain felt during and after the dressing change with visual analog scale (VAS) and a questionnaire. Results: Patients allocated in Group A healed faster than the Group B. Questionnaires and VAS analysis showed lower pain felt, lower intake of pain drugs and lower infection rate in the Group A than the Group B. Analysis of coast showed lower dressing change in Group A than the Group B. Conclusion: We believe that the use of tabotamp is a very viable alternative to improve healing.